Correlation of periodontal status and bone mineral density in postmenopausal women: A digital radiographic and quantitative ultrasound study - S B Vishwanath; Veerendra Kumar; Sheela Kumar; Pratibha Shashikumar; Y Shashikumar; Punit Vaibhav Patel (Wolters Kluwer Medknow Publications, 2011)
Background: Data suggest that postmenopausal women with osteoporosis are at an increased risk for periodontal attachment loss and tooth loss; however, the extent of relationship between these two diseases is still not clear. Aim: The aim of the study was to evaluate the correlation of periodontal status and bone mineral density (BMD) in postmenopausal women. Materials and Methods: The study population included 60 postmenopausal women aged 50-60 years (mean±SD: 55.5±3.4 years). Periodontal status was examined by plaque index, bleeding index, probing depth, and clinical attachment level (CAL). Digital panoramic radiograph was taken to measure the maxillary and mandibular alveolar bone density values. Skeletal (calcaneal) BMD was measured by quantitative ultrasound technique for T-score values. The recorded data for T-score, maxillary and mandibular alveolar bone densities, and periodontal status were subjected to statistical analysis for correlation and regression procedures. Results: The results showed that mandibular alveolar (r=0.907, P<0.001) and maxillary alveolar bone density (r=0.898, P<0.001) had significant positive correlation with calcaneal T-score. Probing depth (r=-0.316, P<0.05), bleeding index (r=-0.277, P<0.05), and plaque index (r=-0.285, P<0.05) showed weak but significant negative correlation with calcaneal T-score and alveolar bone density of both the jaws, whereas CAL showed weak correlation with T-score which could not reach to a statistically significance level (r=-0.221, P>0.05). Conclusion: Calcaneal BMD was related to alveolar bone loss and, to a lesser extent, to clinical attachment loss, implicating postmenopausal bone loss as a risk indicator for periodontal disease in postmenopausal women.